OBTAINMENT OF A REDUCED KINETIC MECHANISM FOR BIODIESEL SURROGATES USING DIRECTED RELATION GRAPH AND SENSITIVITY ANALYSIS (Revista Interdisciplinar de Pesquisa em Engenharia, 2017)
Combustion plays a significant role for transforming energy, and its better understanding contributes to the reduction of pollutants emission, fuel efficiency and stability. Biodiesel is an alternative to the diesel derived from oil. Since biodiesel composition is too complex to be modeled directly, studies are frequently concentrated in biodiesel surrogates, such as Methyl Butanoate (MB). Efficient numerical simulations of reactive flows, such as combustion, depends on the existence of detailed kinetics mechanisms for fuels. However, detailed mechanisms can have tens or hundreds species and hundreds or thousands reactions, which induces significant stiffness to the system of equations. Consequently, there is the need to develop reduced mechanisms with fewer variables and moderate stiffness, maintaining a good level of accuracy of the model. The aim of the present work is to develop reduced mechanisms for MB, applying the Directed Relation Graph (DRG), which is a method that shows the coupling of species through a coefficient based on the reaction rate. Graph search algorithms and some sort of sensitivity analysis are also applied to the skeletal mechanism developed by DRG to further eliminate species and reactions. The advantage of using these methods is the elimination of redundant species and reactions, decreasing the computational cost needed to solve the chemical equations, of about two orders of magnitude for MB, making the numerical simulation of combustion of high chain fuels feasible.